Engineering Thermoanaerobacterium aotearoense SCUT27/Δldh with pyruvate formate lyase-activating protein (PflA) knockout for enhanced ethanol tolerance and production. (July 2021) - Fu, Hongxin; Luo, Sheng; Dai, Kaiqun; Qu, Chunyun; Wang, Jufang
Graphical abstract: Highlights: pflA knockout enhanced ethanol tolerance and production in T. aotearoense SCUT27/ Δldh . The ethanol/acetate ratio increased 2.16-fold when compared to the parental strain. Oxidative decarboxylation of pyruvate via Pfor is favorable over Pfl for ethanol production. Immobilized-cell fermentation was employed to further improve the ethanol production. The highest ethanol production (45.01 g/L) in T. aotearoense SCUT27 was obtained. Abstract: Thermophilic anaerobic bacteria have received increasing interest as a promising bioprocessing platform for bioethanol production due to their broad substrate range and higher operating temperature. However, ethanol concentration is still lower than the commercial requirements on account of the high by-product formation and low ethanol tolerance. Our previous transcriptome analysis showed the gene expression level of pyruvate formate lyase-activating protein (PflA) was significantly down-regulated when Thermoanaerobacterium aotearoense SCUT27/ Δldh was stimulated by various concentrations of ethanol. Based on this, we constructed the mutant strain T. aotearoense SCUT27/ Δldh / ΔpflA, which not only possesses higher ethanol tolerance and production but also has enhanced ethanol/acetate ratio that is important for economical ethanol production. Compared to T. aotearoense SCUT27/ Δldh, the mutant strain could resist to 5% (v/v) exogenous ethanol and produce 49 % more ethanol (38.82 g/L vs. 26.05 g/L) in 5-L bioreactor. In addition, the final concentration of ethanol reached 45.01 g/L by immobilized cell fermentation, which is the highest value obtained in T. aotearoense SCUT27. Simultaneously, the ethanol/acetate ratio of the mutant strain achieved 6.82, which was 2.16-fold higher than that of the parental strain.